The effects of active Bavachin mixt. - libido from natural plant on serum copper, zinc and iron content and Hb levels in elite female handball athletes after high intensity summer training - Zhang, Y.; Chen, X.; Lin, S.; Li, J. (2001)
In order to study the effects of active bavachin mixt.- Libido from natural plant on the content of athletes` serum Cu, Zn and Fe and the level of Hb, 12 elite female handball athletes took the Libido capsules from the beginning to the end of their one-month summer training. The athletes` vein blood were drawn respectively before summer training, on the seventh and on the thirtieth day of summer training. Then the contents of Hb were determined and the serum Cu, Zn and Fe were measured by PE 3300 Atomic Absorption Spectrometer. The results showed that 1. The content of serum Zn made no significant difference during the whole summer training. 2. In the first week of training, the content of serum Cu and Cu/Zn ratio had no evident change and made no significant difference. However, by the end of summer training, both of them decreased significantly (P<0.05). 3. The content of serum Fe increased significantly in the first week (P<0.05), but this significant difference disappeared with the accomplishment of the whole training. 4. The content of Hb dramatically decreased in the first week (P<0.01), but gradually increased during the successive weeks, and even made special significant difference by the end of the summer training (P<0.01). The results indicate that: (1) Libido can maintain the level of serum Zn after high intensity sports training. (2) Libido can fast stimulate the Fe storage in the body and make the level of serum Fe increase significantly in a very short time. (3) Libido can resist the decrease of Hb conducted by high intensity sports training and make the content of Hb increase significantly so as to avoid sports anemia.